2004
DOI: 10.1016/j.otohns.2004.06.350
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression of Thymic Stromal Lymphopoietin in Nasal Mucosa and Nasal Polyps

Abstract: Nasosinusal polyposis (NP) is an inflammatory disease, with higher incidence in asthmatic patients than nonasthmatic, especially in aspirin-intolerant asthmatics. Corticoids are the first line of treatment of NP. The research objective was to demonstrate the existence of different degrees of inflammation in the NP associated or not with asthma, and its different response to corticoid treatment.Methods: Our sample consisted of 80 patients with NP, 19 of whom were assigned to the control group and 61 to the expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Sauer et al reported increased expression of TSLP in nasal polyps when compared with control sinonasal mucosa,22 and overexpression of TSLP in a mouse model induces many features of allergic airway inflammation 23. In addition, stimulation of airway epithelial cell lines with IL-4, IL-13, or TLR3 agonist up-regulates expression of TSLP in vitro 24.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sauer et al reported increased expression of TSLP in nasal polyps when compared with control sinonasal mucosa,22 and overexpression of TSLP in a mouse model induces many features of allergic airway inflammation 23. In addition, stimulation of airway epithelial cell lines with IL-4, IL-13, or TLR3 agonist up-regulates expression of TSLP in vitro 24.…”
Section: Discussionmentioning
confidence: 99%
“…While AMCase and eotaxin-3 are epithelial-derived mediators that directly induce eosinophil tissue infiltration, TSLP is a cytokine that interacts with the adaptive immune system via dendritic cells. Sauer et al reported increased expression of TSLP in nasal polyps when compared with control sinonasal mucosa, 22 and overexpression of TSLP in a mouse model induces many features of allergic airway inflammation. 23 In addition, stimulation of airway epithelial cell lines with IL-4, IL-13, or TLR3 agonist up-regulates expression of TSLP in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Examples include the B-cell–activating factor, which regulates local immunoglobulin production, and thymic stromal lymphopoietin, which modulates dendritic cell function. Expression of these factors is increased in CRSwNP [28,29]. …”
Section: Crs and Epithelial Innate Immunitymentioning
confidence: 99%